Model Matematis Bioadsorben dari Tongkol Jagung Termodifikasi Belimbing Wuluh sebagai Pengolahan Limbah Logam Cu Artifisial - Novan Sandhi Pradana; Firly Firmalya; Ketut Sumada (Jurnal Ilmiah Teknik Kimia, 2026)
Harmful pollutants found in waste include the heavy metal Cu (Copper). Methods that can be used to reduce the heavy metal content of copper include the adsorption process. This adsorption methods was chosen because this process does not produce toxins and the raw materials for adsorbent are more economical such as corn cobs. Corn cobs have a carbon content of 43,42% and have a sufficiently high porous structure. This research aims to determine a compatible mathematic model on the process of adsorption of Cu waste with corn cobs bioadsorbent. The process of making bioadsorbents uses star fruit organic matter as an activator to increase absorption of copper heavy metals. The copper heavy metal adsorption process is carried out by adding the bioadsorbent to artificial liquid waste with adsorbent mass variations of 2.5, 5, 7.5, 10, 12.5 grams and varying harvesting times from 40 to 120 minutes. The results of the analysis using the Atomic Absorption Spectrophotometry (AAS) method revealed that the percentage of copper metal absorption by the best bioadsorbent is 89.55%. This percentage was observed with an adsorbent mass addition of 12.5 grams and a contact time of 120 minutes. Based on the calculations of the mathematical model of heavy metal Cu adsorption by activated carbon from corn cobs using the Langmuir Isotherm model, the resulting equation is y = 0.5497x + 9.968 with a value of R²= 0.994.